Choroidal Thickness Changes After Intravitreal Antivascular Endothelial Growth Factor Therapy for Age-Related Macular Degeneration: Ranibizumab Versus Aflibercept - Gharbiya, Magda; Cruciani, Filippo; Mariotti, Cesare; Grandinetti, Francesca; Marenco, Marco; Cacace, Vittorio (Journal of ocular pharmacology and therapeutics, 2015)
To compare the changes in subfoveal choroidal thickness (CT) in eyes with neovascular age-related macular degeneration (nAMD) treated with intravitreal ranibizumab or aflibercept. In this retrospective case series, the medical records of 28 patients with nAMD treated with at least 3 consecutive monthly injections of ranibizumab (0.5 mg/0.05 mL) or aflibercept (2 mg/0.05 mL) between December 2013 and June 2014 and who were followed up for at least 3 months were reviewed. Subfoveal choroidal thickness was measured using enhanced depth imaging optical coherence tomography. Choroidal thickness decreased over time in the aflibercept group, but was unchanged throughout the study in the ranibizumab group. At each time point, the decrease was significantly greater in aflibercept-treated eyes compared with ranibizumab-treated eyes (P<0.05). No significant change in best-corrected visual acuity (BCVA) was seen in either group during follow-up. There was no correlation between change in choroidal thickness and age, sex, duration of previous antivascular endothelial growth factor treatment, number of previous injections, spherical equivalent, baseline choroidal thickness, and the BCVA outcome in either group. Subfoveal choroidal thickness appeared to decrease significantly in eyes with nAMD during 3 months of aflibercept treatment. No corresponding decrease in choroidal thickness occurred in ranibizumab-treated eyes.